Sea trials of the Seaturns 1:4 scale wave energy converter (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Sea trials of the Seaturns 1/4-scale wave energy converter have been carried out between October 2023 and January 2025 at the Ifremer test site of Sainte-Anne du Portzic, near Brest (France). This wave energy converter technology was developed pursuing simplicity and reliability for all development stages of the project: design, manufacturing, installation and operations. It is made of a cylindrical floater and an innovative anchoring system maximizing the rotational motion of the cylinder around its axis (i.e. the pitch). Inside the floater is a water pendulum and two air-filled chambers. The rotation of the floater and the motion of the water pendulum induce cycles of high and low pressure in these chambers, thus generating an air flow through a turbine directly coupled to a generator to produce electricity. Following various tests in wave tank, these sea trials aimed at validating the performance and reliability of the demonstrator in a marine and operational environment. First, the Seaturns demonstrator working principle is presented. The collaboration between Seaturns, the technology developer, and Ifremer (French Institute of Research for ocean science and technology), the site manager, during the trials is described, along with the experimental set up of the test site and the demonstrator, including wave and wind monitoring, motion sensors and load cells. Then, the demonstrator behavior is analyzed in relation with the sea state for several PTO settings, showing a strong influence of the wave significant height and energetic period on the pitch amplitude, which drives the air flux through the PTO, and therefore the performance of the prototype. Results of mooring tension according to sea states and tidal level are also presented, including storm events (Ciarán, Frederico, …).These trials enabled to collect significant data and validate the Seaturns concept in a real offshore environment, before a future deployment at full-scale on another sea test site.